ELF Learners’ Perception of Internet Media on English Speaking Skill - uddarozat, Rofi (Jurnal Perspektif, 2025)
The aim of this study is to investigate the perceptions of EFL learners regarding the impact of internet media on their English-speaking skills. Utilizing a descriptive qualitative design, interviews were conducted with five EFL from diverse nationalities with different backgrounds. The EFL were asked about the impact and their opinion on this new globalized net and how it has impacted their own growth. The findings indicate that internet media, particularly through exposure of various forms of online content such as YouTube, games, and social media, contributes significantly to improvements in vocabulary, pronunciation, and overall language skills. Moreover, challenges such as the lack of conversation partners and psychological barriers were highlighted as impediments to active speaking practice. The study reveals that while internet media is a valuable tool for linguistic development, it may not fully address the interactive nature of oral communication. To summarize, integrating structured speaking opportunities, enhancing confidence, and offering guidance on media usage in formal educational settings are recommended.